2013
DOI: 10.2478/v10222-012-0080-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Antioxidant Activity of Commercial Honeys, Before and After In-Vitro Digestion

Abstract: Honey is a rich source of antioxidant and antiseptic compounds including Maillard reaction products, vitamins, carotenoids and polyphenols. The objective of the present study was to determine the effect of digestion on the antioxidant activity of a range of honey samples including two economy brands (Tesco and Lidl), a premium Irish brand (Fainne Oir Fine Foods) and a New Zealand Manuka honey. Samples were subjected to an in-vitro digestion which simulates the human gastric and intestinal digestion system. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 15 publications
4
24
2
1
Order By: Relevance
“…As shown in the table, the TPC of MH was 1.27 mg GAEq/g honey, until it decreased about 6-fold in the DMH (0.203 mg GAEq/g honey). Similar results were found by O'Sullivan et al [16], who monitored how the total content of polyphenols in different types of commercial honey changed, finding that, of the four types observed, even if Manuka honey had greatest amount of phenolic compounds, after in vitro gastrointestinal, it lost the greatest amount of phenolic compounds. Regarding the effects of gastrointestinal digestion on honey, there are no further studies, but, in several other food matrices, a significative decrease in the phenolic compounds with respect to the undigested sample was noted.…”
Section: Total Phenolic Compounds and Antioxidant Activitysupporting
confidence: 85%
See 4 more Smart Citations
“…As shown in the table, the TPC of MH was 1.27 mg GAEq/g honey, until it decreased about 6-fold in the DMH (0.203 mg GAEq/g honey). Similar results were found by O'Sullivan et al [16], who monitored how the total content of polyphenols in different types of commercial honey changed, finding that, of the four types observed, even if Manuka honey had greatest amount of phenolic compounds, after in vitro gastrointestinal, it lost the greatest amount of phenolic compounds. Regarding the effects of gastrointestinal digestion on honey, there are no further studies, but, in several other food matrices, a significative decrease in the phenolic compounds with respect to the undigested sample was noted.…”
Section: Total Phenolic Compounds and Antioxidant Activitysupporting
confidence: 85%
“…The TAC in MH, evaluated with FRAP and TEAC, was 261.73 and 251.89 µmol TEq/100 g honey, respectively, and was lowered in the sample representing the bioaccessible intestinal fraction to values of 119.81 and 114.67, respectively. The DPPH test, as in the studies of O'Sullivan et al [16] and Seraglio et al [27], showed a greater decrease in the undigested and the digested sample, suggesting that it is more specific to phenolic compounds than the other two methods used. In fact, the TAC value obtained from the MH (86.479 µmol TEq/100 g honey) decreased by approximately seven times (11.8214 µmol TEq/100 g honey) in DMH as the trend ofTPC and TFC.…”
Section: Total Phenolic Compounds and Antioxidant Activitymentioning
confidence: 87%
See 3 more Smart Citations